A Bibliometric Analysis on Blockchain Technology Literature in Academic Journals - Riska Nur Rosyidiana; Prinintha Nanda Soemarsono; Dani Egi Raharjo (Universitas Airlangga, 2019)
A blockchain is a revolutionary system that connects computer networks in a decentralized and distributed manner. Blockchain allows the process of current transactions to be peer-to-peer (P2P) without relying on a single server. Once entered, information can never be erased. The blockchain contains a certain and verifiable record of every single transaction ever made. This study evaluated the development of research publications in the implementation process and future trend of Blockchain Technology. The aim of this study is to assist researchers in creating a theoretical framework and to provide a preliminary source of references in research mapping in this field. All research publications related to the implementation and future trend of Blockchain Technology in the Scopus database were analyzed using several bibliometric indicators. The authorship, number of citations, journal sources, publishers, institutions, and countries, year of publication, categories, and author keywords were examined.